Analytical toxicology for clinical, forensic, and pharmaceutical chemists - Brandenberger, H.; Maes, R. A. A. 1937- (W. de Gruyter, 1997)
Aimed at toxicologists and pharmacists involved in analytical work, this text provides critical evaluations of analytical possibilities to help with the choice of methods.
Keywords: Analytical toxicology.; Poisons -- Analysis.; elektronické knihy; electronic books